ANALYSIS OF APOPTOSIS FACTORS IN PATIENTS WITH PREINVASIVE AND INVASIVE CERVICAL CANCER - P. I. Kovchur; E. V. Bachidze; O. V. Kurmyshkina; T. O. Volkova (Опухоли женской репродуктивной системы)
This article assesses the disturbance degree of apoptotic program in patients with preinvasive and invasive cervical cancer by investigating the expression level of genes of caspases-3, -6, -8 и -9 in mononuclear cells of periphery blood and in tumor tissue on the two regulating levels – on mRNA level (transcriptional) and proteolytic activity (post transcriptional). 75 patients with stage III of cervical intraepithelial neoplasias (CIN) III  (middle age of 32,9 ± 7,4),45 patients with stage IA (31,3 ± 6,0), 21 – with stage II (43,6 ± 13,2), 15 – with stage III–IV (46,9 ± 11,1) have been examined. The control group has been formed from 30 almost healthy donors without any cervical pathology and papilloma human virus (control 1) and 30 patients with a preinvasive and microinvasive cervical cancer (control 2). It has been found that in proportion of progress of cervix cancer, the membranous expression of CD95 increases in MPB – fraction (peripheral blood monocytes) when the a CIN and initial stages of cervix cancer, more than two times. Herewith number CD95+-lymphocytes is positively correlated with stage of cervical cancer (r = 0,91; R2  = 0,82; p << 0,01). It has been found out that the activity gain of caspase-8 (r = 0,92; R2  = 0,86; p << 0,01), caspase-6 (r = 0,77; R2 = 0,59; p << 0,01) and reduction activity of caspase-9 (r = –0,60;  R2 = 0,36; p < 0,01) in mononuclear cells of peripheral blood pointed out on the sensitivity increase to Fas-induced apoptosis. Opposite, in tumor tissue, beginning from CIN stage III, apoptosis-resistant phenotype is formed, it were defined by the expression of caspase-3 (r = –0,72; R2 = 0,52, p < 0,01), caspase-6 (r = –0,59; R2 = 0, 38; p < 0,01) и caspase-9 (r = –0,67; R2 = 0,45; p < 0,01) by mRNA level and proteolytic activity. It has been shown, that the cervical cancer development is accompanied by multilateral disturbances of apoptotic processes, which are realized in decreased function of caspases and multilateral resistance of tumor cells in against signals of apoptosis. The obtained results give an opportunity to examine the genes of caspase as a probable prospective biomarkers in complex diagnostic of a CIN and early diagnosis of a cervical cancer (in combination with morphological criteria and other molecular markers of viral origin)